2015
DOI: 10.1177/1076029614568715
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Dose Vitamin D3on Soluble P-Selectin and hs-CRP Level in Patients With Venous Thromboembolism

Abstract: High plasma level of P-selectin is associated with the development of venous thromboembolism (VTE). Furthermore, supplementation of vitamin D could decrease thrombotic events. Hence, this study was designed to examine whether the administration of vitamin D can influence the plasma level of P-selectin in patients with VTE. In the randomized controlled trial, 60 patients with confirmed acute deep vein thrombosis and/or pulmonary embolism (PE) were randomized into the intervention (n = 20) and control (n = 40) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Furthermore, based on our previous studies, in our center the rate of vitamin D deficiency was reported as about 60%–65%. Therefore, we can assume a homogeneous level of vitamin D in our population …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on our previous studies, in our center the rate of vitamin D deficiency was reported as about 60%–65%. Therefore, we can assume a homogeneous level of vitamin D in our population …”
Section: Discussionmentioning
confidence: 99%
“…The second study was a prospective randomized clinical trial in which we examined for the first time the effect of an intramuscular single dose of 300,000 IU vitamin D among 20 patients in the intervention group and 40 patients in the control group during a 1‐month period. Results indicated that vitamin D supplementation was not able to significantly reduce hs‐CRP or P‐selectin . However, this study included some limitations.…”
Section: Discussionmentioning
confidence: 78%
“…Results of recent trials assessing the effects of VitD supplementation on the risk of thromboembolism were inconclusive [62][63][64]. In the Multiple Environmental and Genetic Assessment (MEGA) case-control study which included 2506 patients with venous thrombosis, thrombotic risk was 37% lower in those supplemented with various vitamins including VitD [62].…”
Section: Vitamin D and Thrombosismentioning
confidence: 99%
“…However, in a large cohort of postmenopausal women (n=36282) from the Women's Health Initiative, daily supplementation with calcium and VitD failed to reduce the overall risk of thromboembolism [63]. Even when high doses (300,000 IU) of VitD were given intramuscularly, in a small group of patients with proven deep vein thrombosis and pulmonary embolism, observed reduction in plasma concentrations of P-selectin and high-sensitive Creactive protein (hs-CRP) did not reached statistical significance [64]. Additional information could be expected from the ongoing Vitamin D and OmegA-3 Trial (VITAL) and that is why the results of this investigation are eagerly awaited [65].…”
Section: Vitamin D and Thrombosismentioning
confidence: 99%